Particle tracking using dynamic water level data - Gao, Yuan, author; Sale, Thomas, advisor; Ronayne, Michael, committee member; Blotevogel, Jens, committee member (Colorado State University. Libraries, 2017)
Movement of fluid particles about historic subsurface releases and through well fields is often governed by dynamic subsurface water levels. Factors influencing temporal changes in water levels include changes in river stage, tidal fluctuation, seasonal transpiration from trees and pumping of wells. Motivations for tracking the movement of fluid particles include tracking the fate of subsurface contaminants and resolving the fate of water stored in subsurface aquifers. This research provides novel methods for predicting the movement of subsurface particles relying on dynamic water level data derived from continuously recording pressure transducers or an analytic solution based on a Theis superposition model that predicts water levels about dynamically operated wells in well fields. For particle tracking at field sites without pumping conditions, firstly, the dynamic water level data obtained from sites in Kansas City, Missouri; Pueblo, Colorado; and Honolulu, Hawaii are employed. The basic idea is to use water-level data from at least three wells to solve for the plane of the water table and obtain the hydraulic gradient in the x and y directions. Secondly, based on the Darcy's equation, the position of a particle is moved in the x and y directions at each time step. Finally, by connecting all the positions of particle together, the path line of particle flowed in the subsurface can be obtained. Homogeneous, isotropic and homogeneous, anisotropic conditions with retardation were considered for particle tracking at the three sites in this research. Also, consideration is given to natural degradation of contaminants in the subsurface. By assuming the degradation of contaminants at each site follows first order kinetics, the distance the contaminants can flow within the minimum concentration requirement and the time when the concentration of contaminants arrived at the minimum concentration requirement can be obtained. Based on the results from this research, river stage, seasonal transpiration and precipitation, and tidal fluctuation at three sites all have great influences on local groundwater flow. The great changes of water-level in short periods caused by seasonal recharge and discharge and seasonal transpiration and precipitation make the hydraulic gradient changed greatly, subsequently make the direction of groundwater flow altered. For the site near a harbor, tidal fluctuations make the groundwater level changed, which correspondingly have the hydraulic gradient and direction of groundwater flow changed. Initial review of water-level in rose chart indicates a range of groundwater flow direction and gradient with time. This indicates a wide range of temporally changing flow directions and gradients. Surprisingly, despite temporal variation in flow directions, the net groundwater flow at all field sites is largely constant in one direction. From the results of particle tracking and rose charts, groundwater flow mainly follows the direction of the hydraulic gradients with large magnitudes in rose charts, but does not follow every direction of hydraulic gradient in the rose chart. The explanation for this phenomena is the main direction of groundwater flow is driven by hydraulic gradient with large magnitude, because the time interval for each groundwater flow driven by each hydraulic gradient is the same, according to the Darcy's equation, hydraulic gradient in the direction with small magnitude cannot drive particles flow long enough to make particles flow away from the main direction. Moreover, this research uses dynamic pumping well data to test how particles move under dynamic pumping conditions in well fields. Based on superposition of the Theis solution in both space and time, this research uses an analytical solution to resolve how fluid particles move about wells under dynamic pumping conditions. The results from particle tracking under dynamic pumping conditions in this research provide: firstly, a relatively uniform capture zone in the well field. Secondly, even under continuous pumping and injection conditions, groundwater will not flow far away from the well. Thirdly, particle tracking provides groundwater positions and delineates the position of storage water under dynamic pumping and injection condition.
Keywords: movement; subsurface contaminant; particle tracking; groundwater